Youtube as a New Means of Marketing Communication - Zavodna, Lucie Sara; Zavodny Pospisil, Jan (Communications - Scientific Letters of the University of Zilina, 2017)
This paper discusses a new trend in marketing communication represented by a new generation of YouTubers. The target group, young people aged 12-16, is absorbed in following the YouTubers who set the trends in shopping; not only what one should buy but also when. There is often some kind of cooperation between the YouTubers and some of the well-known companies that provide sample bags with their products for the YouTubers for free. This paper analyzes the Czech YouTube environment, YouTube blogs from channels in English and the results of a questionnaire survey which was conducted on a sample of students who could be described as the Generation Y.
Keywords: trends; marketing communication; YouTube; internet